The Great Law, or, The Body of laws of ye province of Pennsilvania territorys thereunto belonging : past at an assembly at Chester als Upland the seaventh day of ye 10th month (1682)
"What is known as the 'Great Law' is a series of statutes enacted by Pennsylvania's first legislature that met in Upland, now Chester, on December 4-7, 1682." Pennsylvania Historical & Museum Commission website.